TYPOLOGY OF FINANCIAL MANAGEMENT STRATEGIES IN ISLAMIC EDUCATIONAL INSTITUTIONS: A SHARIAH ECONOMIC PERSPECTIVE - Ahmad Rifaudin; Bayu Pramono; Zainal Muttaqin; Agus Gunawan; M A Tihami (PT. Jurnal Center Indonesia Publisher, 2025)
The Industrial Revolution 4.0 era and COVID-19 pandemic have accelerated the adoption of digital technology in education, yet Islamic educational institutions face unique challenges in balancing technological modernization with the preservation of authentic Islamic values and scholarly traditions. This research employs the theoretical framework of Resource-Based View (RBV) and the Islamic concept of tawhid to analyze how religious values can serve as strategic resources in creating sustainable competitive advantage through digital technology integration. The objective of this research is to analyze the integration strategy of digital technology with Islamic values in educational innovation and develop an implementation framework to achieve sustainable competitive advantage for Islamic educational institutions. The research utilizes qualitative methods with a library research approach through content analysis and narrative synthesis of international journals, academic books, and current research publications validated through source triangulation from various academic databases. The research findings identify three integration models (content, pedagogical, and systemic), competitive advantage achievement strategies through value-based differentiation and network effects, and a five-dimensional implementation framework (philosophical, structural, operational, evaluative, and adaptive) that can create unique value propositions in learning ecosystems combining spiritual, intellectual, and technological intelligence. The research limitation lies in the library research approach that does not involve empirical validation through case studies or direct implementation in Islamic educational institutions therefore it is recommended to conduct further research with a mixed-method approach that combines theoretical analysis with implementation case studies in various types of Islamic educational institutions to test the effectiveness of the developed framework in diverse practical contexts